PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN BUDAYA ORGANISASI TERHADAP KINERJA GURU - Aini, Ilmi; Hariri, Hasan; Rini, Riswanti (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2024)
The aim of this article is to examine the influence of the transformational leadership style of school principals and organizational culture on teacher performance in schools. The articles used in this literature review were obtained through Google Scholar by using keywords such as "transformational leadership," "organizational culture," and "teacher performance." Based on the literature review findings, the researchers discovered that transformational leadership style and organizational culture have a positive and significant impact on teacher performance.